Analisis Kualitas Rancangan Point of Sale Menerapkan Metode Mean Squared Error - Fithrie Soufitri; Ellanda Purwawijaya (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The development of the business prompted the company to always strive to improve the quality of products and services to consumers. The service can purchase goods was done electronically and can also be done online or electronic commerce. Implementation of business solutions is a commitment to improve its corporate customers a competitive advantage in terms of efficiency, effectiveness, performance, and business development. The research purpose is to analyze the quality of point of sale (POS) designs to support a purchasing service system that can help Nasi Kapau Unidar restaurants. This creation begins with data collection using the mean squared error (MSE) method with a flowchart approach and Unified Modeling Language (UML) with the result of the accuracy with mean squared error of 0.44.